Maqashid Syariah-Based Religious Coping Strategies in Matrifocal Families: Enhancing Family Resilience among Indonesian Migrant Workers - Muna Yastuti Madrah; Muchamad Coirun Nizar; Suyanto; Setiowati, Erni Agustina; Sartika, Diana Dewi; Fiddini, Sukna; Saleh, Muhammad Aunurrochim Mas'ad (Universitas Islam Negeri Raden Intan Lampung, 2026)
Indonesian migrant worker matrifocal families face significant pressures, including emotional strain, shifting gender roles, and economic uncertainty. This study investigates the influence of maqāṣid al-sharī‘ah-based religious coping strategies on family resilience within matrifocal families in Jambearum Village, Kendal, Central Java. Utilizing a qualitative methodology, data were gathered through in-depth interviews, observation, and document analysis with ten couples and thirty community members. The results reveal that matrifocal families employ two interrelated dimensions of religious coping: Problem-Focused Coping (PFC), demonstrated through children's religious education (hifdz al-nasl) and prudent asset management (hifdz al-māl); and EmotionFocused Coping (EFC), manifested in worship, prayer, dhikr, sabr, and tawakkul (hifdz al-nafs, hifdz al-‘aql, and hifdz al-dīn). Integratingmaqāṣid al-sharī‘ahinto both PFC and EFC produces a distinctively Islamic model of family resilience, addressing both material and spiritual challenges. This approach, which has been largely overlooked in previous research on matrifocal migrant worker families, provides practical implications for policymakers and religious communities supporting these families.